2019
DOI: 10.17306/j.afs.0657
|View full text |Cite
|
Sign up to set email alerts
|

Effect of drying and milling modes on the quality of white rice of an Indonesian long grain rice cultivar

Abstract: Background. Many studies have revealed the susceptibility of long grain rice to breaking during milling, while others have demonstrated the variation in the yield of head rice due to different rough rice drying methods. Thus, this study aims to determine appropriate drying and milling methods to improve the head rice yield and nutritional quality of long grain rice. Materials and methods. A series of drying experiments were performed on rough paddy rice employing shallow bed, oven and sun drying methods. Then,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…The required moisture content of 14% (dry basis) was obtained in 5 to 9 hours from 28% initial moisture content depending on the type of drying pads used. Kumoro et al (2019) conducted another similar experiment from 7.00 am to 12.00 noon by evenly spreading rough paddy onto a concrete floor and tarpaulin (white and black) with the rice layer thickness 2 to 5 cm. Hellevang ( 2004) reported that plastic sheets could result in condensed water and tend to hold them in low places; thus, not suitable for drying pads.…”
Section: Effect Of Different Drying Pads On Moisture Removalmentioning
confidence: 99%
“…The required moisture content of 14% (dry basis) was obtained in 5 to 9 hours from 28% initial moisture content depending on the type of drying pads used. Kumoro et al (2019) conducted another similar experiment from 7.00 am to 12.00 noon by evenly spreading rough paddy onto a concrete floor and tarpaulin (white and black) with the rice layer thickness 2 to 5 cm. Hellevang ( 2004) reported that plastic sheets could result in condensed water and tend to hold them in low places; thus, not suitable for drying pads.…”
Section: Effect Of Different Drying Pads On Moisture Removalmentioning
confidence: 99%
“…During drying, the heat flow induces the development of moisture and temperature gradients and thermal stress inside the rice kernel, leading to the formation of fissures on the kernel. Usually, fissured kernels break easily during milling causing a serious reduction in the head rice yield, cooking qualities and market value (Kumoro et al, 2019).…”
Section: Food Dairy and Home Economic Researchmentioning
confidence: 99%
“…At moisture contents less than 14%, the grain becomes brittle and cracks or break during milling. Both instances lead to reduction in head rice yield (Schluterman and Siebenmorgen, 2007;Akowuah et al, 2012;Kumoro et al, 2019). Generally, a good quality paddy constitutes about 55% head rice, 15% broken, 20% husk, and 10% bran.…”
Section: Response Of Varieties To Millingmentioning
confidence: 99%
“…Rice cracking was known as sun-cracking by earlier researchers, latter research led to the observation that rice cracking was due to moisture absorption of dried rice (Schluterman and Siebenmorgen, 2007;Akowuah et al, 2012). Some studies in different varieties found that rice cracking begins at moisture content below 14.2 and 18.3% for crack resistant and crack susceptible varieties, respectively (Kumoro et al, 2019). Another factor that may cause paddy to crack before harvest is nonsynchronous blooming which leads to uneven grain maturity (Schluterman and Siebenmorgen, 2007;Akowuah et al, 2012;Kumoro et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation